AB0901 Trends in Paediatric Rheumatology Referral Times and Disease Activity Indices over A Ten-Year Period among Children with Juvenile Idiopathic Arthritis: Results from the Childhood Arthritis Prospective Study (CAPS). (10th June 2014) - McErlane, F.; Foster, H.E.; Carrasco, R.; Baildam, E.M.; Chieng, A.S.E.; Davidson, J.D.; Ioannou, Y.; Wedderburn, L.R.; Thomson, W.; Hyrich, K.
Abstract : Background: The medical management of children and adolescents with juvenile idiopathic arthritis (JIA) has advanced significantly over the past ten years, favouring early therapy with the goal of remission. The UK BSPAR Standards of Care (2009) stipulate that children with JIA should see a paediatric rheumatology team (PRh) within ten weeks of symptom onset and within four weeks of referral. It is not known how often these standards are met or whether they have impacted on outcomes. Objectives: This analysis aims to describe trends in referral times, baseline disease severity, treatment times and one-year outcomes over a ten-year period among children with JIA enrolled in CAPS. Methods: CAPS is a prospective inception cohort of children with new-onset inflammatory arthritis recruiting from seven UK PRh centres. This analysis included all children recruited between 2001 and 2011 with at least one year of follow-up. The cohort was divided into four groups by year of diagnosis (2001-2004, 2005-2006, 2007-2008, 2009-2011). At baseline, median referral times, disease pattern (oligoarticular, polyarticular or systemic onset), and disease activity indices (active joint count (AJC), JADAS and CHAQ) were determined for each group. Time to first definitive treatment was determined within each disease pattern. The proportions of children achieving minimal disease activity (MDA) (Magni-Manzoni, 2008) within each cohort were compared. Values across the four groups were compared using linear and logistic regression, adjusting for PRh centre and disease pattern. Results: 1066 children were included with disease pattern documented at baseline in 987 (93%). Median time from both symptom onset and date of referral to first PRh appointment did not vary significantly across the study period. Only ∼20% were seen within ten weeks of symptom onset and ∼50% within four weeks of referral (Table 1 ) with a significant trend towards longer waiting times for first appointments in more recent years. However, there was a positive trend towards earlier definitive treatment once children were assessed by PRh, reaching significance in polyarticular-pattern disease. This was associated with a trend towards a higher proportion of children with MDA at one-year in the later years of study. Conclusions: Despite guidelines emphasising early assessment by PRh, approximately half of children with new-onset JIA were not seen within four weeks of referral, with only 20% within ten weeks of symptom onset. The reasons for the former may be related to PRh service pressures and capacity issues and the latter most likely multifactorial, relating to both public and physician education. However, it is encouraging to see more rapid introduction of treatment and associated improvements in outcome. Further research is necessary to understand why approximately one-third of children continue to have active disease one year following first PRh assessment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3680